Analysis of the impact of nutritional status of pregnant women on neonatal complications - Mindarsih, Eko; Setyaningsih, Dewi; Suwarsi, Suwarsi; Alvarado, Angelito (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: Neonatal complications are a health problem that affects neonatal mortality. Most deaths occur in the first week of life; the causes are asphyxia, infection, jaundice, and congenital abnormalities. The nutritional status of pregnant women has a significant influence on neonatal complications. However, few studies still explore the combined impact of the analysis of three factors of maternal nutritional status on various neonatal complications. Objective: This study aims to analyse the impact of the nutritional status of pregnant women on neonatal complications. Method: This study is an observational analytical study with a cross-sectional design conducted in the Ngemplak I Health Centre area, Sleman, DIY. The study sample consisted of 140 pregnant women who met the inclusion criteria, selected using a purposive sampling technique. Data were collected through questionnaires and KIA books, and then analysed using the Chi-Square test with a significance value of p <0.05. Results: The results showed that maternal BMI was significantly associated with asphyxia (p = 0.011; OR = 1.168) and jaundice (p = 0.045; OR = 0.320), while anaemia and CED were not significant for neonatal complications. Conclusion: The Nutritional status of pregnant women, BMI significantly affects neonatal complications, while anaemia and chronic energy disease do not significantly affect neonatal complications.fluenced by factors such as asphyxia, jaundice, infection, and congenital abnormalities. The nutritional status of pregnant women plays an important role in determining the health of the mother and baby.